Strategy of Advertising Tax Collection in the Digitalization Era on Badan Pendapatan Daerah of DKI Jakarta - Eka Rofiyanti; Ika Muji Lestari; Istamkhuja Olimovich Davronov; Alian Natision; Krishantoro Krishantoro (Yayasan Ilomata, 2022)
The phenomenon of this research is that in the digital era, many people switch to promoting their products to social media, which is one of the causes of the decrease in billboard taxes. This study aims to find out the right strategy in the billboard tax collection in the digital era by the Regional Revenue Agency of DKI Jakarta. The research method used is the descriptive qualitative method. Data sources include primary data, namely data from interviews, and secondary data, namely target data and billboard tax realization from 2016-2020. The results of this study indicate that (1) The billboard tax collection strategy in the digitalization era in the future will lead to billboard data collection, optimization of billboard objects and tax applications such as e-tax (2) the power of billboard taxes in the digital era lies in the development of digital technology and cooperation between the government, the private sector and the community; and (3) obstacles and challenges from billboard taxes in the digitalization era are the number of taxpayers who have not mastered technology and are not obedient in paying their tax obligations. The suggestion in this study is that the Regional Revenue Agency of DKI Jakarta forms a fieldwork team to conduct more thorough data collection, take advantage of technological developments, lead the comprehensive campaign to taxpayers, and provide strict sanctions to taxpayers who do not obey and install illegal billboards and (3) obstacles and challenges from billboard taxes in the digitalization era are the number of taxpayers who have not mastered technology and are not obedient in paying their tax obligations. The suggestion in this study is that the Regional Revenue Agency of DKI Jakarta forms a fieldwork team to conduct more thorough data collection, take advantage of technological developments, lead the comprehensive campaign to taxpayers, and provide strict sanctions to taxpayers who do not obey and install illegal billboards and (3) obstacles and challenges from billboard taxes in the digitalization era are the number of taxpayers who have not mastered technology and are not obedient in paying their tax obligations. The suggestion in this study is that the Regional Revenue Agency of DKI Jakarta form a fieldwork team to conduct more thorough data collection, take advantage of technological developments, work a comprehensive campaign to taxpayers, and provide strict sanctions to taxpayers who do not obey and install illegal billboards.